2003
DOI: 10.1097/00042752-200301000-00006
|View full text |Cite
|
Sign up to set email alerts
|

CogSport: Reliability and Correlation with Conventional Cognitive Tests Used in Postconcussion Medical Evaluations

Abstract: CogSport is a highly reliable cognitive function test when administered to healthy young adults and elite athletes. CogSport measures similar cognitive functions as conventional tests used commonly in concussion research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
200
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(210 citation statements)
references
References 16 publications
7
200
1
2
Order By: Relevance
“…The 1-year reliability estimate for RT clin (ICC = 0.645) compares favorably with that of concurrently measured RT comp . Although the ICC for RT clin obtained in this study is somewhat lower than ICCs in the literature for computerized reaction time measures over retest intervals of 1 hour to 2 weeks, 3,11,12 it is comparable with or greater than published values for time intervals ranging from 45 days to 2 years. 21,23 25 as desirable for making decisions about individual change in the context of sport-related concussion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The 1-year reliability estimate for RT clin (ICC = 0.645) compares favorably with that of concurrently measured RT comp . Although the ICC for RT clin obtained in this study is somewhat lower than ICCs in the literature for computerized reaction time measures over retest intervals of 1 hour to 2 weeks, 3,11,12 it is comparable with or greater than published values for time intervals ranging from 45 days to 2 years. 21,23 25 as desirable for making decisions about individual change in the context of sport-related concussion.…”
Section: Discussionsupporting
confidence: 52%
“…[6][7][8][9][10] Reaction time measures provide one of the most sensitive indices of cognitive changes after concussion in both athletic and general head injury populations. 11,12 Decreased speed of information processing is thought to account for the cognitive performance deficits seen after concussion. 11 Impaired reaction time after concussion parallels the persistence of postconcussive symptoms 7,9 and may persist beyond resolution of self-reported symptoms and clinical findings.…”
mentioning
confidence: 99%
“…[76][77][78][79][80][81][82][83][84] One critique of the computerized tests is that the vast majority of studies have been conducted by the developers of the tests, which raises some concern for bias, because some independent study results have suggested slightly less reliable results. 85,86 A few of these computerized tests have been widely adopted at all levels of sport participation.…”
Section: Neuropsychological Testingmentioning
confidence: 99%
“…HBCS-Psychomotor speed was measured with two tests being part of a standardised language independent computerized battery of cognitive tests (CogState1, version 3.0.5). This battery has been validated and shown to be a sensitive indicator of mild impairments in the following cognitive domains: psychomotor speed, attention, working memory and episodic learning and memory (Collie et al, 2001(Collie et al, , 2003Darby et al, 2002). In the tasks participants were asked to pay attention to playing cards on a computer screen.…”
Section: Lbc1936-mentioning
confidence: 99%